An Unfused‐Core‐Based Nonfullerene Acceptor Enables High‐Efficiency Organic Solar Cells with Excellent Morphological Stability at High Temperatures - Li, Shuixing; Zhan, Lingling; Liu, Feng; Ren, Jie; Shi, Minmin; Li, Chang‐Zhi; Russell, Thomas P.; Chen, Hongzheng (Advanced materials (Weinheim), 2018)
Most nonfullerene acceptors developed so far for high‐performance organic solar cells (OSCs) are designed in planar molecular geometry containing a fused‐ring core. In this work, a new nonfullerene acceptor of DF‐PCIC is synthesized with an unfused‐ring core containing two cyclopentadithiophene (CPDT) moieties and one 2,5‐difluorobenzene (DFB) group. A nearly planar geometry is realized through the F···H noncovalent interaction between CPDT and DFB for DF‐PCIC. After proper optimizations, the OSCs with DF‐PCIC as the acceptor and the polymer PBDB‐T as the donor yield the best power conversion efficiency (PCE) of 10.14% with a high fill factor of 0.72. To the best of our knowledge, this efficiency is among the highest values for the OSCs with nonfullerene acceptors owning unfused‐ring cores. Furthermore, no obvious morphological changes are observed for the thermally treated PBDB‐T:DF‐PCIC blended films, and the relevant devices can keep ≈70% of the original PCEs upon thermal treatment at 180 °C for 12 h. This tolerance of such a high temperature for so long time is rarely reported for fullerene‐free OSCs, which might be due to the unique unfused‐ring core of DF‐PCIC. Therefore, the work provides new idea for the design of new nonfullerene acceptors applicable in commercial OSCs in the future. A new nonfullerene acceptor (DF‐PCIC) is designed and synthesized by utilizing noncovalent interactions. Organic solar cells (OSCs) with DF‐PCIC as the acceptor exhibit the best efficiency of 10.14% with a high fill factor of 0.72. More importantly, excellent morphological stability is achieved for DF‐PCIC‐based devices, which is meaningful for the future practical applications of OSCs.